Ecological and economic aspects of expenditure of hunting farms in Zaporizhzhia region - Yavorska, Tetiana; Яворська, Тетяна Іванівна; Sobolevska, Olha (My University, 2022)
The purpose of the article is to study the composition and cost structure of hunting farms in the Zaporizhzhia region and consider the economic and environmental aspects of their formation. The method of analysis and synthesis revealed the dynamics of changes in the costs of hunting farms over five years (2015, 2016, 2017, 2018, 2019). Using the method of comparison, the main trends in the change of individual loss items are identified. Methodology. The classification of costs, their dynamics and structure on 37 hunting farms of Zaporizhzhia region are given. The studied farms differ in different forms of use of hunting grounds. Thus, as of January 1, 2020, 6 farms were part of the Ukrainian Society of Hunters and Fishermen, 20 – belonged to the enterprises of the State Forestry Agency of Ukraine, the remaining 11 – were part of other private and public hunting organizations. A vertical and horizontal analysis of costs was conducted, which revealed an increase in their volume throughout the structure, without significant changes in the structure itself. There is a tendency to reduce the share of costs for the protection, reproduction and accounting of wild animals and the management of hunting grounds. Instead, the costs of maintaining the current activities of hunting farms are increasing. The results of the study showed that the main part of the costs of hunting farms in Zaporizhzhia region (almost 80 %) consists of the cost of wages and a single social contribution, operation and maintenance of vehicles, hunting buildings and structures and costs associated with the purchase of weapons, ammunition and other costs. The costs of environmental activities are decreasing, among which the costs of biotechnical measures play an important role. The share of expenditures on biotechnical measures for the conservation and reproduction of wild animals in total expenditures decreased from 14.5 % in 2015 to 11.8 % in 2019. Practical consequences. The study found that the current costly model of hunting in the Zaporizhzhia region, and in Ukraine as a whole, does not meet market relations and inhibits the development of effective economic and environmental hunting. Its formation was influenced by the following factors: imperfection of hunting legislation; non-compliance with European standards; excessive number of hunting grounds in use and lack of a clear mechanism for payment for their use; poaching; lack of programs for breeding wild animals, control of predators and clear requirements for the hunting service; low level of hunting culture and ethics. The current hostilities in the Zaporizhzhia region further complicate the environmental situation. Value/originality. Economic evaluation of hunting farms should take into account, in addition to estimating the direct costs and revenues of hunting farms, their total environmental, economic and social role. This is confirmed by foreign experience. For its implementation there is a need to develop a new methodology.
Keywords: hunting farms; classification of costs; composition and structure of costs; costs of biotechnical measures; costs of protection and reproduction; costly management model